Analysis of screening decisions in inventory models with imperfect quality items. Issue 21 (2nd November 2021) - Hauck, Zsuzsanna; Rabta, Boualem; Reiner, Gerald
Abstract : We consider an Economic Order Quantity (EOQ) model with imperfect quality items. All the items undergo a quality screening process for which both the cost and the defect detection rate depend on the time devoted to this operation. Contrary to most previous research in the field, the speed of screening is taken as a decision variable in the presented model jointly with the order quantity. Additionally, we introduce various functional forms for the screening cost and defect detection functions. In particular, nonlinear forms lead to nonconvexities in the total cost function consisting of multiple cost components, e.g. inspection cost, penalty costs, etc. We solve the model analytically for a selected set of assumptions and provide numerical examples and sensitivity analysis. The results provide interesting insights. While lower screening costs motivate longer screening times, the effectiveness of this operation is only obtained in combination with the reliability of the defect detection method. It is also observed that reducing return rates and improving customer satisfaction can be achieved by adjusting the operational parameters, without a significant increase in system cost or new investments.